Behind the shattered glass - Alexander, Tasha (New York Minotaur Books, 2014)
When their neighbor, a young aristocrat, is murdered, Lady Emily Hargreave and her husband Colin examine the motives of those closest to him to catch a killer amidst dark secrets and forbidden passions.
Includes an excerpt from the author's The counterfeit heiress (pages 289-302).
Originally published in hardcover in 2013.
115269
Keywords: Hargreaves, Emily -- Lady (Fictitious character) -- Fiction; 1800-1899; Upper class -- England -- Fiction; Murder -- England -- 19th century -- Fiction; Manners and customs; Mayfair (London, England) -- Fiction; England -- Social life and customs -- 19th century -- Fiction; England -- Social life and customs -- Fiction; England -- London -- Mayfair; Historical fiction; Detective and mystery fiction; Fiction; Mystery fiction; Historical fiction